Advertising Design in Vietnam’ Character: Variation of Visual Design Elements in Outdoor Advertising - Ha, Nguyen Thi Viet (Current Approaches in Science and Technology Research Vol. 2, 2021)
Visual Design factors have given special attention, and have even become a trend, spreading to the art of design, particularly in outdoor advertising. In the era of International Integration of Vietnam, there is a large number of changes in advertising posters, and Visual Design factors plays a very important role in this process. Advertising poster is integrated with visual languages, creating a totally new outlock on aestheticism. The research analyses how Visual Art factors have been expressed in outdoor advertising, especially in graphic elements, from concept to execution which is used for brands available in Vietnamese market from 2017 till now (April 2021). The area of research is Ho Chi Minh City where there is a diversity of market trends and also a place which is greatly and quickly influenced by new trends in Art and Design. This is also considered as the place that can absorb quickly new trends of Arts and Culture in creating Advertising campaigns for Vietnamese market. Besides, Ho Chi Minh city also plays as the leader in development of modern society for Vietnamese; there are many contruction projects for sky building, plazas, living space, privacy, to store belongings, and to comfortably live and work for urban population.